2021
DOI: 10.1186/s13287-021-02247-3
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the pericyte transcriptome in ischemic skeletal muscles

Abstract: Background Peripheral arterial disease (PAD) affects millions of people and compromises quality of life. Critical limb ischemia (CLI), which is the most advanced stage of PAD, can cause nonhealing ulcers and strong chronic pain, and it shortens the patients’ life expectancy. Cell-based angiogenic therapies are becoming a real therapeutic approach to treat CLI. Pericytes are cells that surround vascular endothelial cells to reinforce vessel integrity and regulate local blood pressure and metabol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“… 10 We identified proliferative CAFs expressing myosatellite cell markers PAX7 14 and MYF5 15 ( Figure 1D , pink) that were present only in tumors originating in the oral cavity (ACC7, ACC21, and ACC22), consistent with the presence of submucosal muscle tissue in the oral cavity. We identified myofibroblasts ( Figure 1D , green) expressing pericyte markers CDH6 and MCAM 16 that were seen across tumors. Two other CAF clusters corresponded to inflammatory CAF subtypes.…”
Section: Resultsmentioning
confidence: 99%
“… 10 We identified proliferative CAFs expressing myosatellite cell markers PAX7 14 and MYF5 15 ( Figure 1D , pink) that were present only in tumors originating in the oral cavity (ACC7, ACC21, and ACC22), consistent with the presence of submucosal muscle tissue in the oral cavity. We identified myofibroblasts ( Figure 1D , green) expressing pericyte markers CDH6 and MCAM 16 that were seen across tumors. Two other CAF clusters corresponded to inflammatory CAF subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…Mural cell ontogeny is known to be heterogeneous and varies depending on tissue and context (Chen et al, 2016). The predominant view is that local proliferation of pericytes is induced following injury, as shown by upregulation of genes involved in mitotic cell division (Teng et al, 2021). Likewise, neointimal smooth muscle cells have been shown to undergo phenotypic switching and consequent cell proliferation in response to vascular injury (Herring et al, 2014;Nemenoff et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…3F). Gene set enrichment analysis performed using STRING (Szklarczyk et al, 2019) with genes upregulated in cluster 2 (versus 0) yielded various GO biological process terms (referred to as GO terms) associated with mural cell functions (Teng et al, 2021) in the ischemic muscle (Fig. 4A), including blood circulation, blood vessel development, cell junction assembly, anatomical structure morphogenesis and tube development.…”
Section: Macrophages Adopt Mural Cell-like Characteristics In Ischemi...mentioning
confidence: 99%
“…Since CD146 has been described as a suitable marker for pericyte isolation, in particular in skeletal muscle and non-muscle tissues [10,26], and our data on human skin sections showed that among the different perivascular markers CD146 is the most ubiquitously and strongly expressed, we decided to use CD146 as marker for human dermal pericyte isolation. Isolated CD146 + pericytes were then cultured in vitro and characterized for specific marker expression (Fig.…”
Section: Cultured Cd146-positive Pericytes Displayed Markers Of Periv...mentioning
confidence: 99%